Nusyuz as the Cause of Domestic Violence: A Comparative Study of Islamic Law and Criminal Law - Rafianti, Fitri; Pratama Sinaga, M. Hary Angga (International Journal of Law, Environment, and Natural Resources, 2023)
This article aims to explain the dynamics of Nusyuz as one of the reasons why domestic violence (KDRT) is allowed in the perspective of Islam, and further elaborates with a comparative study in the context of Criminal Law. This research uses a qualitative method with an approach to Islamic Law and Criminal Law in Indonesia. The data was obtained through in-depth exploration of regulations contained in the Qur'an, Hadith, laws, and other necessary legal sources through literature review and documentation. There are three main questions that this research seeks to answer: First, how is the legal regulation of Nusyuz in the context of Islamic Law; Second, how is the correlation between Nusyuz and domestic violence cases; Third, how is the settlement of Nusyuz cases related to domestic violence cases in the perspective of Criminal Law. This research shows that, first, the regulation of Nusyuz is very clearly stated through legal sources in the context of Islamic Law, but there are often misunderstandings in interpreting commandments, prohibitions, and choices of verses. Second, the correlation between Nusyuz and KDRT requires awareness of experiences of violence against women and close people in the household environment, although the phenomenon of violence against women is always identified with the nature of private space where the Nusyuz of husband and wife is a private space that, when known publicly, becomes a shame that must be hidden without considering the applicable legal provisions. Third, Nusyuz is often associated with cases of domestic violence if a wife who is nusyuz gives her husband various rights in treating her. Starting from the right to hit her, distance her, not provide her with good material and spiritual support, and finally the husband also has the right to divorce her. Of course, the wife remains the victim of exploitation, both physically, mentally, and sexually. This is exacerbated by the absence of clear rules in limiting the husband's rights, making it very possible for the husband to act arbitrarily in this matter. The solutions to prevent domestic violence include: First, understanding the obligations and responsibilities of both husband and wife in the household. Second, always being with the wife and inviting her to chat. Third, always saying good words and making her happy. Fourth, not hurting or hitting the wife in the face. The above things will not happen if the husband and wife understand their duties and responsibilities in the household and do not interpret verses as legal evidence for justifying domestic violence due to the inability to understand legal evidence that is sometimes only partially read.